Facile regioselective decomposition of tosylhydrazones: an application towards the synthesis of alpha-lipoic acid - Chavan, Subhash P.; Kale, R. R.; Pasupathy, K. (Synlett, 2005)
A facile regioselective decomposition of tosylhydrazones using NaOH as a base in refluxing isopropyl alcohol is described. This finding has been Successfully applied towards the synthesis of (&PLUSMN;)-α-lipoic acid (1).
Keywords: alpha-lipoic acid; Olefins; Regioselectivity; tosylhydrazones

Hydroformylation of olefins using dispersed molecular catalysts on solid supports - Pagar, N. S.; Deshpande, R. M.; Chaudhari, Raghunath V. (Catalysis Letters, 2006)
A new method for heterogenization of metal complex catalysts by precipitation of its water-soluble analogue as a Gr.2 metals (Ca, Sr or Ba) salt on porous supports has been proposed. This technique yields a highly dispersed catalyst having a significantly higher activity (TOF) for hydroformylation of olefins compared to other known heterogenized catalysts. The catalyst can be recycled with ease.
Keywords: carbon support; Heterogenization; Hydroformylation; Olefins; Rhodium

Contemporary avenues in catalytic P-H bond addition reaction: a case study of hydrophosphination - Koshti, Vijay; Gaikwad, Shahaji R.; Chikkali, Samir H. (Coordination Chemistry Reviews, 2014)
Remarkable advances and current state-of-the-art developments in catalytic hydrophosphination of alkenes and alkynes are reviewed. The challenges in constructing a C P bond with a special emphasis on metal catalysed (asymmetric) hydrophosphination are highlighted. Only those systems that unambiguously proceed via P H bond addition across a C-C/X (X = O, N, S) multiple bond have been covered in this overview. Reviewed examples support the assumption that either strongly chelating ligands or reaction products that act as ligands, enhance the rate of hydrophosphination. The asymmetric variant of this transformation allows installation of p-chiral [enantiomeric excess (ee) up to 82%] as well as C-chiral (ee up to 99%) centres. The limited spectroscopic, mechanistic data and OFT calculations point at two distinctly different mechanisms. In case of hydrophosphination, the metal undergoes oxidative addition and reductive elimination steps (in general), thus changing the oxidation state from M(0) to M(II) and back to M(0). Whereas in asymmetric hydrophosphination it is proposed that the oxidation state of the metal remains unaltered throughout the catalytic cycle. The examples described in this overview showcase the real power of catalytic hydrophosphination in constructing various phosphorus compounds, which may initiate a new era in organo-phosphorus chemistry. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alkynes; Asymmetric hydrophosphination; Hydrophosphination; Metal catalyzed hydrophosphination; Olefins; P-H bond addition

Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Phosphorus ligands in hydroformylation and hydrogenation: a personal account - Tewari, Tanuja; Kumar, Rohit; Chandanshive, Amol C.; Chikkali, Samir H. (Chemical Record, 2021)
Metal-catalyzed hydroformylation and hydrogenation heavily rely on ligands, among which phosphorous ligands play a pivotal role. This personal account presents a selection of three distinct classes of phosphorous ligands, namely, monodentate meta-substituted phosphinites, bis-phosphites, and P-chiral supramolecular phosphines, developed in our group. The synthesis of these ligands, isolation, characterization, and their performance in transition metal-catalyzed hydroformylation, isomerizing hydroformylation, and asymmetric hydrogenation of olefins is summarized. The state of the art development in iron-catalyzed hydroformylation of alkenes and our contributions to the field is discussed. Use of phosphines enabled iron-catalyzed hydroformylation of alkenes under mild conditions. Thus, this account demonstrates the central role of phosphorus ligands in industrially relevant transformations such as hydrogenation and hydroformylation. The seemingly matured field of ligand discovery still holds significant potential and will steer the field of homogeneous catalysis.
Keywords: Homogeneous catalysis; Hydroformylation; Hydrogenation; Olefins; Phosphorus ligands